A Prospective, Randomized, Controlled Trial to Assess the Efficacy of a Multi-Disciplinary Screening, Brief Intervention and Referral to Treatment Program for Patients with Fractures of the Oral and Maxillofacial Region Because of Alcohol-Related Injuries in the Emergency Department - Ja Heon Koo; Hyung Jun Song; Jun Hee Lee; Jae Hyun Kim; Jung Woo Nam; Jae Eun Im (Journal of Trauma and Injury)
Purpose We have implemented a multi-disciplinary Screening, Brief Intervention and Referral to Treatment (SBIRT) protocol to prevent individuals who sustained alcohol-related traumatic injuries. We therefore conducted this single-center, prospective, randomized, controlled trial (RCT) to assess its efficacy. Methods All the enrolled patients (n=30) were randomized to either the SBIRT group or the control group. In the current RCT, the proportion of the patients who reduced the amount of alcohol consumption and those who received a specialized treatment served as primary outcome measures. Moreover, changes in a 3-item version of the Alcohol Use Disorders Identification Test Consumption (AUDIT-C), Severity of Dependence Scale (SDS) and Kessler Psychological Distress Scale (K-6) scores at 3 months from baseline served as secondary outcome measures. Results At 3 months, the proportion of the patients who reduced the amount of alcohol consumption was significantly higher in the SBIRT group as compared with the control group (86.7% vs. 57.1%, p=0.02). Moreover, the proportion of the patients who received a specialized treatment was also significantly higher as compared with the control group (26.7% vs. 1.4%, p=0.01). Furthermore, there were significant differences in changes in the AUDIT, SDS and K-6 scores at 3 months from baseline between the two groups (p<0.05). Conclusions In conclusion, our results indicate that the SBIRT is effective in reducing hazardous and harmful levels of drinking, the degree of alcohol dependence and that of psychological distress in at-risk drinkers.